Analisis Perbedaan Persepsi Masyarakat terhadap Investasi Emas Sebelum dan Sesudah Kenaikan Harga - Nabila Nandayanti; Aisyah Mega Benazira; Nurul Azmi Muhamad Tauhid; Pingkan Salsa Hadiansyah; Mia Lasmi Wardiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Evaluating changes in public perceptions of gold investment before and after price increases is the objective of this study. The background of this study rests on the assumption that gold price volatility can affect an individual's interest in and view of gold as an investment vehicle. This study used a quantitative approach by distributing questionnaires using a Likert scale to 50 respondents, the results of which were analyzed using the paired sample t-test. The results of the analysis show that there is no statistically significant difference in people's perceptions before and after the gold price increase (significance value 0.363 > 0.05). The findings of this study indicate that the public still views gold as a safe and stable investment asset in the long term, regardless of price changes in the short term. The results of this study can be used as a reference by market participants and financial planners to understand the tendency of public attitudes towards gold investment.